Legal Review of the Resolution of Waqf Land Disputes Resulting from the Annulment of a Waqf Pledge Deed: : A Study in Bireuen Regency - Citra Shinta Meutia Denies; Iman Jauhari; Suhaimi Suhaimi (International Journal of Law, Crime and Justice, 2026)
Waqf is a legal act involving the dedication of privately owned property for religious purposes and/or public welfare in accordance with Islamic law. Article 16 paragraph (2) of Law Number 41 of 2004 concerning Waqf stipulates that waqf objects must consist of movable or immovable assets legally owned by the waqif (the person who endows the property). Furthermore, Article 4 of Government Regulation Number 28 of 1977 emphasizes that land designated as waqf must constitute legally owned land that is free from any encumbrances, legal attachments, seizure, or disputes. However, in practice, waqf disputes still occur due to the dedication of land with problematic ownership status, as found in Juli District, Bireuen Regency. This study aims to analyze the resolution of waqf disputes arising from the annulment of a Waqf Pledge Deed based on the Supreme Court Decision Number 0314/Pdt.G/2014. This research employs a normative-empirical juridical method using statutory and case approaches. The study utilizes primary, secondary, and tertiary legal materials, supported by field data obtained through interviews, which are subsequently analyzed qualitatively. The results indicate that the resolution of waqf land disputes at the Bireuen Sharia Court is conducted by examining the validity of the elements of waqf, particularly the legal ownership status of the endowed land. The Beunyot Village Religious Affairs Office (KUA) in Juli District, acting as the Official Registrar of Waqf Pledge Deeds (Pejabat Pembuat Akta Ikrar Wakaf/PPAIW), issued the Waqf Pledge Deed after considering the fulfillment of formal requirements, including the existence of the waqif, nazhir (waqf administrator), and waqf object. However, the Bireuen Sharia Court declared the deed invalid and nullified it by law because the endowed land was not personally owned by the waqif, thereby contradicting the statutory provisions governing waqf. It is recommended that the Ministry of Religious Affairs, through the Beunyot Village KUA as the PPAIW, conduct more thorough verification of land ownership status before issuing Waqf Pledge Deeds. Furthermore, nazhir, community leaders, and religious counselors should enhance public education regarding waqf regulations to ensure that society understands the legal requirements of valid waqf and to prevent future waqf disputes.